2009
DOI: 10.2298/apt0940111z
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of lactic acid bacteria community during the development of mature sourdough

Abstract: In order to follow the composition and changes in lactic acid bacteria (LAB) population of rye flour sourdough that was continuously propagated by a repeated inoculation, sixty-two strains of LAB were isolated and characterized. The LAB were the only bacteria detected, both at the end of the second propagation step and in the stage of mature sourdough (after two weeks of continuous daily refreshment). The stable ecological system in rye sourdough could be established from the second propagation step onward. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Weckx et al [ 83 ] who studied rye sourdough reported that it took shorter time to reach maturity as compared to wheat and spelt sourdough, possibly due to the different rates of enzymatic activities. In mature sourdough, a range between 10 7 and 10 8 colony-forming units (cfu) g −1 [ 103 ] or sometimes more than 10 8 cfu g −1 [ 4 , 56 , 87 ] of LAB can be found. Therefore, it can be said that LAB population increases as pH reduces and finally both reach a plateau when sourdough mature [ 12 ].…”
Section: Microbial Communities In Different Sourdough Startersmentioning
confidence: 99%
“…Weckx et al [ 83 ] who studied rye sourdough reported that it took shorter time to reach maturity as compared to wheat and spelt sourdough, possibly due to the different rates of enzymatic activities. In mature sourdough, a range between 10 7 and 10 8 colony-forming units (cfu) g −1 [ 103 ] or sometimes more than 10 8 cfu g −1 [ 4 , 56 , 87 ] of LAB can be found. Therefore, it can be said that LAB population increases as pH reduces and finally both reach a plateau when sourdough mature [ 12 ].…”
Section: Microbial Communities In Different Sourdough Startersmentioning
confidence: 99%